A study on income tax deduction and opinion in india - ROBERT. P, WILLIAM; A, ABINASH (The journal of contemporary issues in business and government, 2020)
The research paper titled “The role of tax payers in India and the growth of Indian economy. The objective is to study the factors influencing the taxpayers perception towards the Indian tax system. Descriptive research is applied using a convenience method of sampling 80 respondents. The data is collected from taxpayers, employees, businessmen. The tools used here are mean analysis, frequency analysis, t-test, Anova and regression. It is found that the majority of the age group is 36-45 years. The objective of the study is to find out the measure cost of compliance with the income tax of Indian corporations. The allowances, deductions, exemptions, rebates and reliefs were given as per legal regulations according to the law.